Customizable and adaptive quantum processors : theory and applications - Nedjah, Nadia; Macedo Mourelle, Luiza de (Boca Raton : CRC Press, 2023)
"This book presents the architecture of a quantum coprocessor that can be implemented on hardware and embedded into our personal computers to accelerate the resolution of hard complex problems. As far as the authors are concerned, this work is a pioneer as it is the first and only one that attempts a hardware implementation of a quantum coprocessor that executes quantum operation as a user directives inserted within a traditional program"--
OCLC-licensed vendor bibliographic record.
Keywords: Quantum computing; Microprocessors; COMPUTERS / Operating Systems / General; COMPUTERS / Programming / Software Development; MATHEMATICS / Arithmetic